Dietary Fatty Acid Regulation of the NLRP3 Inflammasome via the TLR4/NF-κB Signaling Pathway Affects Chondrocyte Pyroptosis. (4th May 2022) - Jin, Xin; Dong, Xin; Sun, Yingxu; Liu, Ziyu; Liu, Li; Gu, Hailun
Abstract : Dietary fatty acid (FA) content and type have different effects on obesity-associated osteoarthritis (OA), but the mechanisms underlying these differences are not fully understood. Inflammation activated by toll-like receptor 4 (TLR4)/nuclear factor- (NF-) κ B signaling and pyroptosis induced by the NLRP3/caspase-1/gasdermin D (GSDMD) signaling pathway play important roles in OA development. Our aim in this study was to observe the effects of dietary FAs on the articular cartilage of obese post-traumatic OA model mice and on chondrocytes stimulated by lipopolysaccharide (LPS) and to determine whether the underlying mechanisms involve TLR4/NF- κ B and NLRP3/caspase-1/GSDMD signaling pathways. Mice were fed high-fat diets rich in various FAs and underwent surgical destabilization of the medial meniscus to establish the obesity-related post-traumatic OA model. LPS-induced SW1353 chondrosarcoma cells were used to mimic OA status in vitro, and TLR4 inhibitors or TLR4 overexpressing lentivirus was administered. Analysis using weight-matched mice and multiple regression models revealed that OA was associated with dietary FA content and serum inflammatory factor levels, but not body weight. Diets rich in n-3 polyunsaturated fatty acids (PUFAs) attenuated OA and inhibited the TLR4/NF- κ B and NLRP3/caspase-1/GSDMD signaling pathways, whereas diets rich in saturated fatty acids (SFAs), monounsaturated fatty acids (MUFAs), or n-6 PUFAs increased OA severity and activated these pathways. In vitro results for SFAs, n-6 PUFAs, and n-3 PUFAs were consistent with the animal experiments. However, those for MUFAs were not. FA effects on the NLRP3/caspase-1/GSDMD pathway were associated with the inhibition or activation of the TLR4 signaling pathway. In conclusion, diets rich in SFAs or n-6 PUFAs can exacerbate obesity-associated OA, whereas those rich in n-3 PUFAs have protective effects against this disease, due to their respective pro-/anti-inflammatory and pyroptotic effects. Further research on dietary FA supplements as a potential therapeutic approach for OA is needed.